A thick coating for steel structures with corrosion and fire resistance

By adopting a thick coating design with a multi-layer structure on the steel structure, the problems of insufficient durability and corrosion resistance of existing coatings are solved, good corrosion resistance and fire resistance are achieved, and service life is extended.

CN119775843APending Publication Date: 2025-04-08SUZHOU DACHENG ENVIRONMENTAL PROTECTION NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411954046.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing steel structure fire-retardant coatings have insufficient durability and poor corrosion resistance, which leads to cracking, peeling or powder removal during use, and the fire-retardant performance decreases accordingly.

Method used

The thick coating design adopts a multi-layer structure, including composite resin-modified zinc-rich primer, thermally insulated and anti-corrosion coating, lightweight fire-resistant coating and finish weather-resistant layer. Through reasonable proportions and the denseness of the interlayer structure, the corrosion resistance and fire-resistant performance of the coating are improved.

Benefits of technology

Maintain good corrosion resistance during long-term use and provide effective flame retardant isolation and fire protection when fire occurs, extending service life and improving overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775843A_ABST
    Figure CN119775843A_ABST
Patent Text Reader

Abstract

The present application belongs to the field of fire protection of chemical steel structures, and more specifically, relates to a thick coating with corrosion resistance and fire resistance for steel structures. A thick coating with corrosion resistance and fire resistance for steel structures, comprising a composite resin modified zinc-rich primer, a heat-insulating anti-corrosion coating, a lightweight fire-proof coating and a finishing weather-resistant layer sequentially arranged on the surface of a steel substrate, wherein the heat-insulating anti-corrosion coating comprises 80-120 parts of a composite resin emulsion, 52.5-76.7 parts of a curing aid, 30-40 parts of a nano-alumina dispersion, 66.5-133.5 parts of an active enhancement powder, 0.3-0.6 parts of an anti-settling agent, and 0.3-0.6 parts of a cellulose ether, wherein the active enhancement powder comprises slag powder, steel slag powder, sodium silicate, basalt flakes and quartz powder. The present application discloses a thick coating with corrosion resistance and fire resistance for steel structures. This coating aims to solve the problems of insufficient durability and poor corrosion resistance of existing thick fire-resistant coatings. The thick coating with corrosion resistance and fire resistance for steel structures has excellent fire-resistant properties and ultra-high salt spray resistance. The coatings have good adhesion and density, good long-term performance, and meet the needs of building fire-resistant coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of fire protection of chemical steel structures, and more specifically, to a thick coating for steel structures with corrosion resistance and fire protection performance. Background Art

[0002] With the rapid development of modern construction industry, steel structure has been widely used in modern buildings such as steel structure parking lots, industrial plants, gymnasiums, stations, airports, bridges, etc. due to its advantages of good mechanical properties, high strength, light weight and high space utilization. However, the corrosion resistance and fire resistance of steel structure itself are very poor, and it is very easy to conduct heat. When the temperature reaches 450℃, its mechanical properties begin to deteriorate, and the deterioration effect becomes more serious with the increase of temperature. When the temperature reaches 580℃, its mechanical strength drops to less than 1 / 2 of the room temperature, which cannot meet the supporting function of buildings and structures. Therefore, in order to prevent the exposed steel from collapsing due to the reduced strength of the steel structure after a fire, thereby causing huge losses to people's lives and property, steel structure buildings must be fire-protected.

[0003] Steel structure fire retardant coatings are divided into two categories based on their working principles: expansion type and non-expansion type. Among them, non-expansion fire retardant coatings do not expand in a fire. They rely on the non-combustibility, low thermal conductivity of the material or the heat absorption and flame retardancy of the material in the coating to delay the temperature rise of the steel. Therefore, thick coatings are usually used to protect steel structures. However, the durability of the coating is insufficient after application. Insufficient adhesion between the coating layers and between the coating and the substrate may lead to cracking or hollowing between the layers. The fire resistance decreases over time, and even powdering and peeling may occur. The coating also has poor corrosion resistance, and long-term use of the underlying layer may cause rust, which may pose a huge safety hazard to the coating. Summary of the invention

[0004] In view of the problems of insufficient durability and poor corrosion resistance of existing fire-resistant thick coatings, the present application provides a thick coating with corrosion resistance and fire resistance for steel structures.

[0005] In the first aspect, the present application provides a thick coating with corrosion resistance and fire resistance for steel structures, which adopts the following technical solution: A thick coating with corrosion resistance and fire resistance for steel structures, comprising a composite resin modified zinc-rich primer, a heat-insulating anti-corrosion coating, a lightweight fire-proof coating and a finishing weather-resistant layer arranged in sequence on the surface of a steel substrate, wherein the heat-insulating anti-corrosion coating comprises, by weight, 80-120 parts of a composite resin emulsion, 52.5-76.7 parts of a curing aid, 30-40 parts of a nano-alumina dispersion, 66.5-133.5 parts of an active enhancement powder, 0.3-0.6 parts of an anti-settling agent and 0.3-0.6 parts of a cellulose ether, wherein the active enhancement powder comprises slag powder, steel slag powder, sodium silicate, basalt flakes and quartz powder.

[0006] By adopting the above technical scheme and designing a multi-layer structure of thick coating for steel structure, which is respectively composed of composite resin modified zinc-rich primer, heat insulation and anti-corrosion coating, lightweight fire retardant coating and finishing weather-resistant layer, the material ratio of each layer is reasonable and the interlayer structure is dense. It can maintain good corrosion resistance in long-term use and provide effective flame retardant isolation and fire protection in the event of fire.

[0007] The composite resin modified zinc-rich primer uses sacrificial zinc powder to prevent rust and has a cathodic protection effect on steel. The composite resin modification can enhance the chemical solvent resistance, corrosion resistance and adhesion, making the coating material have good weather resistance and strong adhesion. The heat insulation and anti-corrosion coating has high bonding strength through the composite resin emulsion and basalt flakes, and forms a multi-layer flaky structure with parallel superposition and good shielding performance. The resin can be divided into several small spaces, effectively improving the stress concentration phenomenon inside the resin. The scales can form a staggered arrangement, which can make the penetration of corrosive media tortuous, thereby delaying the diffusion and The path and time of invading the metal surface can improve the anti-corrosion performance of the coating. By adding nano-alumina dispersion, on the one hand, it has excellent heat resistance and fire resistance, which can significantly improve the density, anti-corrosion and flame retardancy of the paint film. On the other hand, nano-alumina dispersion can improve the dispersibility and interface performance to prevent sedimentation, and ensure the interface compatibility between basalt flakes and composite resin solution. By adding curing aids, anti-settling agents and cellulose ethers, the dispersibility and high and low temperature stability of the thermal insulation and anti-corrosion coating materials can be further improved, and the corrosion resistance of the materials can be improved, so that they can be used in harsh environments with large temperature differences.

[0008] Preferably, the activity enhancing powder also includes quartz sand.

[0009] By adding quartz sand to the active reinforcing powder, the high temperature resistance and chemical stability of the thermal insulation and anti-corrosion coating can be further improved. The small particle size of quartz sand can further enhance the density of the active reinforcing powder in the thermal insulation and anti-corrosion coating, and the quartz sand itself has corrosion resistance.

[0010] The composite resin emulsion comprises silicone acrylate hybrid epoxy resin and silicone emulsion. The mass ratio of silicone acrylate hybrid epoxy resin to silicone emulsion is (1.5-4):1.

[0011] Organic silicon acrylate has good weather resistance and water resistance, but slow room temperature curing rate. Hybrid epoxy resin that is easy to cure at room temperature, its ether bond ortho-carbon and tertiary carbon undergo free radical polymerization, and the epoxy is directly grafted into the acrylic resin before ring opening to prevent excessive -OH from causing explosion gel after ring opening. It has certain storage stability. When curing into film, the ring opening of the epoxy group can greatly improve the interlayer adhesion, and has excellent bonding properties with various materials, making the composite resin emulsion resistant to chemical solvents and anti-corrosion properties. By adding a certain proportion of organic silicon emulsion to the system, the Si-O-Si structure can improve the hardness and cross-linking density of the resin after film formation, improve the density and impact resistance of the material, improve the salt spray resistance, acid and alkali resistance and temperature resistance, and then improve the comprehensive properties of the coating strength and corrosion resistance. Among them, if the content of organic silicon acrylate hybrid epoxy resin is too low, the interlayer adhesion may be insufficient, and hollowing may be easily formed between the layers, affecting the anti-corrosion performance and durability of the material.

[0012] The mass ratio of the composite resin emulsion, the nano-alumina dispersion and the basalt flakes is (2-4):1:(0.2-0.45).

[0013] By using a certain proportion of composite resin emulsion, nano-alumina dispersion and basalt flakes, the heat-insulating anti-corrosion coating maintains good interlayer adhesion and density, forming a barrier layer that can effectively isolate the corrosive medium, greatly increasing the difficulty of the corrosive medium entering the coating film. The introduction of inorganic nano-alumina dispersion improves the heat resistance of the middle coating, and can maintain the adhesion of the high-barrier heat-resistant anti-corrosion coating on the metal surface for a certain period of time, which can significantly improve the anti-corrosion performance of the system and the bonding performance of the fire-retardant coating. Among them, if the content of composite resin emulsion is too low, the adhesion performance is insufficient and the strength is poor. If the content of nano-alumina dispersion is too low, the heat resistance is insufficient, and the dispersion of basalt flakes is weak. The interface effect with the resin is relatively poor, which makes the arrangement of basalt flakes difficult to control, affecting the corrosion resistance of the anti-corrosion coating.

[0014] In a specific embodiment, the finishing weather-resistant layer includes 60-70 parts by mass of silicone acrylate hybrid epoxy resin, 30-40 parts by mass of FEVE emulsion, 33.7-44.7 parts by mass of curing aid, 0.2-0.4 parts by mass of leveling agent, 5-8 parts by mass of nano calcium carbonate and 3-6 parts by mass of color paste.

[0015] The mass ratio of the FEVE emulsion and nano-calcium carbonate is (4-8):1.

[0016] By adopting the above technical solution, the chemical inertness of the coating surface is further improved by adding silicone acrylate hybrid epoxy resin to FEVE resin, and a large number of FC bonds are introduced, which has stronger stability. The introduction of nano calcium carbonate significantly improves the density of the paint film after the resin is cured, prevents powdering and fading, and enhances the weather resistance and color retention of the protective surface layer, as well as the ability to resist various corrosive media, thereby ensuring that the entire fire protection system has excellent weather resistance, can maintain the system's fire protection ability for a long time, and extend the service life. Excessive FEVE emulsion content will cause the coating to be too rigid, lack good elasticity, unstable performance, and severe cracking and peeling.

[0017] In a specific embodiment, the composite resin modified zinc-rich primer includes, by weight, 80-120 parts of composite resin emulsion, 92-108 parts of zinc-rich reinforcing powder, 39.3-47.7 parts of curing aid, and 5-8 parts of nano-alumina dispersion; the zinc-rich reinforcing powder includes slag powder, sodium silicate and zinc powder.

[0018] The mass ratio of the slag powder, sodium silicate and zinc powder is (1.8-4):1:(9-16).

[0019] By adopting the above technical scheme, the silicone acrylic hybrid epoxy resin in the composite resin emulsion enhances the bonding and adhesion of the metal base layer. The introduction of a certain proportion of silicone resin improves the compactness and weather resistance of the paint film, and the excellent salt spray resistance, acid and alkali resistance and temperature resistance. By adding a nano-alumina dispersion suitable for the quality of the primer film, the primer has excellent heat resistance and fire resistance, and the compactness, corrosion resistance and flame retardancy of the paint film are significantly improved. By adding a certain range of inorganic nano-material slag powder and sodium silicate to interact, the channel formed by the volatilization of water after the resin film is formed is cut off, and the sealing effect of the water-based resin coating is significantly improved. Combined with zinc powder, it has a high anti-corrosion effect on the metal surface, and has the advantages of strong bonding with the metal substrate, good salt spray resistance, and good heat and humidity resistance. Among them, too little zinc powder content may affect the salt spray resistance of the primer.

[0020] In a specific embodiment, the curing aid includes a curing agent, a wetting agent, a dispersant, a defoaming agent, a film-forming aid and deionized water.

[0021] By adopting the above technical solution and adding a curing aid, the adhesion and density between the coatings are improved, and the curing rate and production efficiency can be increased.

[0022] In summary, this application has the following beneficial effects: 1. Through the design of the multi-layer structure of thick coating on steel structure, it is composed of composite resin modified zinc-rich primer, heat insulation and anti-corrosion coating, lightweight fire retardant coating and finishing weather-resistant layer. The material ratio of each layer is reasonable and the interlayer structure is dense. It can maintain good corrosion resistance in long-term use and provide effective flame retardant isolation and fire protection in the event of fire.

[0023] The composite resin modified zinc-rich primer prevents rust by sacrificing zinc powder and has a cathodic protection effect on steel. The composite resin modification can enhance the chemical solvent resistance, corrosion resistance and adhesion, making the coating material have good weather resistance and strong adhesion. The thermal insulation and anti-corrosion coating has high bonding strength through the composite resin emulsion and basalt flakes, and forms a barrier effect with parallel superposition of multi-layer flaky structures and good shielding performance. The scales can form a staggered arrangement, which can make the penetration of corrosive media tortuous, thereby delaying the path and time of the corrosive media diffusion and invasion of the metal surface, thereby improving the anti-corrosion performance of the coating. By adding nano-alumina dispersion, the density, corrosion resistance and flame retardancy of the paint film can be significantly improved, the dispersibility and interface performance can be improved to prevent sedimentation, and the interface compatibility between the basalt flakes and the composite resin solution can be ensured.

[0024] 2. Organic silicon acrylate has good weather resistance and water resistance, but slow room temperature curing rate. Hybridized epoxy resin that is easy to cure at room temperature has free radical polymerization on the ortho-carbon and tertiary carbon of the ether bond. It is directly grafted into the acrylic resin before the epoxy ring is opened to prevent the excessive -OH from causing explosive gel after the ring opening. It has certain storage stability. When curing into film, the ring opening of the epoxy group can greatly improve the interlayer adhesion and has excellent bonding properties with various materials, making the composite resin emulsion resistant to chemical solvents and anti-corrosion properties. By adding a certain proportion of organic silicon emulsion to the system, the Si-O-Si structure can improve the hardness and cross-linking density of the resin after film formation, improve the density and impact resistance of the material, improve the salt spray resistance, acid and alkali resistance and temperature resistance, and then improve the comprehensive properties of the coating strength and corrosion resistance.

[0025] 3. By adding silicone acrylate hybrid epoxy resin to FEVE resin, the chemical inertness of the coating surface is further improved, and a large number of FC bonds are introduced, which has stronger stability. The introduction of nano calcium carbonate significantly improves the density of the paint film after the resin is cured, prevents powdering and fading, and enhances the weather resistance and color retention of the protective surface layer, as well as the ability to resist various corrosive media, thereby ensuring that the entire fire protection system has excellent weather resistance, can maintain the system's fire protection ability for a long time, and extend the service life. Excessive FEVE emulsion content will cause the coating to be too rigid, lack good elasticity, unstable performance, and severe cracking and peeling. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1It is a schematic diagram of the overall cross-sectional structure of the thick coating with corrosion resistance and fire resistance provided in Example 1 of the present application and the steel substrate.

[0027] Explanation of the accompanying drawings: 1. Steel substrate; 2. Composite resin modified zinc-rich primer; 3. Thermal insulation and anti-corrosion coating; 4. Lightweight fire retardant coating; 5. Finishing weather-resistant layer. DETAILED DESCRIPTION

[0028] The present application is further described in detail below with reference to the embodiments.

[0029] Some raw materials used in the preparation examples and examples: silicone emulsion model: Dowsil 8016; Curing agent model Aradur 3951; wetting agent model TSF-1700; dispersant model: VK.DP2100; defoamer model: PX-122; film-forming aid model: TEXANOL; nano-alumina dispersion is nano-alumina alcohol dispersion, 5-10nm particle size, 20wt% isopropanol solution; slag powder is ultrafine slag powder (specific surface area ≥ 600 square meters / kg); steel slag powder is ultrafine steel slag powder (specific surface area ≥ 600 square meters / kg); sodium silicate is purchased from Shandong Duofeng Chemical Co., Ltd.; zinc powder brand: FZN30; anti-settling agent model: BYK-R605; cellulose ether is hydroxypropyl methylcellulose purchased from Weifang Lit Composite Materials Co., Ltd.; basalt flakes (80-100 mesh) Brand: NCE; quartz powder (300nm); quartz sand (10-20 mesh); high alumina cement is aluminate cement model: CA50-II (G6); glass powder is low melting point glass powder (200-2000 mesh); hollow glass beads (600 mesh) brand: Synade; barium sulfate model: CX-325; aluminum hydroxide was purchased from Langfang Pengcai Fine Chemical Co., Ltd.; silica ash item number: dy88 purchased from Lingshou County Dongyan Mineral Products Co., Ltd.; light sand is expanded perlite; purchased from Henan Xinyang Changxin Mining Co., Ltd.; FEVE emulsion brand: ZH-01; nano calcium carbonate model: CCR-6525; leveling agent is silicone leveling agent; color paste model: LuconylBlack 0066; silicone acrylic resin model: SH-024.

[0030] The raw materials used in the examples and comparative examples that are not otherwise specified are all conventional products that can be purchased from the market.

[0031] Preparation Example 1 Silicone acrylate hybrid epoxy resin: Take 12g butyl acrylate, 5g ethylene glycol dimethacrylate, 1.8g maleic anhydride and 0.3g γ-aminopropyltriethoxysilane, add 38ml ethyl acetate to react, under the action of azobisisobutyronitrile, react at 70°C for 2h, and obtain a copolymer; at room temperature, add 5g SiO2 sol formed by partial hydrolysis of ethyl orthosilicate, then add 10g E-44 epoxy resin with a mass fraction of 12% and 3g γ-aminopropyltriethoxysilane with a mass fraction of 4%, stir at room temperature, and obtain the silicone acrylate hybrid epoxy resin after the solvent evaporates.

[0032] Example 1 A thick coating with corrosion resistance and fire resistance for steel structure, comprising the following components: a composite resin modified zinc-rich primer 2, a heat insulation and anti-corrosion coating 3, a lightweight fire-proof coating 4 and a finishing weather-resistant layer 5 arranged in sequence on the surface of a steel substrate 1, wherein the composite resin modified zinc-rich primer 2 comprises the following mass components: 100g of composite resin emulsion, 108g of zinc-rich reinforcing powder, 40.9g of curing aid, and 5g of nano-alumina dispersion; wherein the composite resin emulsion comprises 70g of organic silicon acrylate hybrid epoxy resin obtained in Preparation Example 1 and 30g of organic silicon emulsion, and the zinc-rich reinforcing powder comprises slag powder, sodium silicate and zinc powder in a mass ratio of 1.8:1:9; and the curing aid comprises 10g of curing agent, 0.1g of wetting agent, 0.3g of dispersant, 0.2g of defoaming agent, 0.6g of film-forming aid and 29.7g of deionized water; The heat-insulating and anti-corrosion coating 3 is composed of the following mass components: 100 g of composite resin emulsion, 53.4 g of curing aid, 40 g of nano-alumina dispersion, 72.2 g of active reinforcing powder, 0.5 g of anti-settling agent, and 0.5 g of cellulose ether; wherein the composite resin emulsion is the silicone acrylate hybrid epoxy resin and silicone emulsion prepared in Preparation Example 1 in a mass ratio of 1.5:1; the active reinforcing powder includes 20 g of slag powder, 10 g of steel slag powder, 2 g of sodium silicate, 15.2 g of basalt flakes, and 25 g of quartz powder; the mass ratio of the composite resin emulsion, nano-alumina dispersion, and basalt flakes is 2.5:1:0.38; the curing aid is 10 g of curing agent, 0.3 g of wetting agent, 0.4 g of dispersant, 0.3 g of defoaming agent, 0.6 g of film-forming aid, and 41.8 g of deionized water; Lightweight fireproof coating 4: including 110g composite resin emulsion, 103g lightweight composite powder, 107g curing aid, and 35g nano-alumina dispersion; wherein, 80g of the organosilicon acrylate hybrid epoxy resin prepared in Preparation Example 1 and 30g of organosilicon emulsion; the lightweight composite powder is 25g of high-alumina cement, 7g of glass powder, 5g of hollow glass beads, 4g of barium sulfate, 10g of aluminum hydroxide, 1g of silica fume, 0.2g of cellulose ether, and 34.7g of light sand; the curing aid includes 9g of curing agent, 0.3g of wetting agent, 0.3g of dispersant, 0.2g of defoaming agent, 0.5g of film-forming aid, and 23.4g of deionized water; Finishing weather-resistant layer 5: including 65g of water-based silicone acrylate hybrid epoxy resin, 36g of FEVE emulsion, 34g of curing aid, 0.2g of leveling agent, 6g of nano calcium carbonate and 4g of color paste; wherein the curing aid includes 9g of curing agent, 0.3g of wetting agent, 0.3g of dispersant, 0.2g of defoaming agent, 0.5g of film-forming aid and 23.7g of deionized water; First, mix the composite resin modified zinc-rich primer 2 coating evenly in proportion, and evenly apply it on the surface of the steel substrate 1 by rolling, ensuring that the thickness is 2 mm; mix the heat-insulating anti-corrosion coating 3 coating evenly, and spray it on the surface of the dried and cured composite resin modified zinc-rich primer 2, ensuring that the thickness is 18 mm; mix the lightweight fire-retardant coating 4 coating evenly, and spray it on the surface of the dried and cured heat-insulating anti-corrosion coating 3; ensuring that the thickness is 10 mm, mix the finishing weather-resistant layer 5 coating evenly, and spray it on the cured surface of the lightweight fire-retardant coating 4, ensuring that the thickness is 1 mm.

[0033] Example 2 The difference between this embodiment and Embodiment 1 is that the thickness of the composite resin modified zinc-rich primer 2 coating applied on the surface of the steel substrate 1 is 2 mm; the heat-insulating and anti-corrosion coating 3 coating is evenly mixed and sprayed on the surface of the composite resin modified zinc-rich primer 2 after drying and curing, with a thickness of 18 mm; the lightweight fire-retardant coating 4 coating is evenly mixed and sprayed on the surface of the heat-insulating and anti-corrosion coating 3 after drying and curing; ensuring that the thickness is 20 mm, the finishing weather-resistant layer 5 coating is evenly mixed and sprayed on the surface of the cured lightweight fire-retardant coating 4, ensuring that the thickness is 1 mm.

[0034] Example 3 The difference between this embodiment and embodiment 1 is that the active enhancement powder further includes 33.5 g of quartz sand.

[0035] Example 4 The difference between this embodiment and embodiment 1 is that the zinc-rich reinforcing powder is slag powder, sodium silicate and zinc powder in a mass ratio of 4:1:11.

[0036] Example 5 The difference between this embodiment and embodiment 1 is that the zinc-rich reinforcing powder is slag powder, sodium silicate and zinc powder in a mass ratio of 4:1:6.8.

[0037] Example 6 The difference between this embodiment and embodiment 1 is that the composite resin emulsion is the silicone acrylate hybrid epoxy resin and silicone emulsion prepared in preparation example 1 in a mass ratio of 3:1.

[0038] Example 7 The difference between this embodiment and embodiment 1 is that the composite resin emulsion is the silicone acrylate hybrid epoxy resin and silicone emulsion prepared in preparation example 1 in a mass ratio of 1:1.

[0039] Example 8 The difference between this embodiment and embodiment 1 is that the composite resin emulsion is organic silicon acrylate resin and organic silicon emulsion.

[0040] Example 9 The difference between this embodiment and embodiment 1 is that the thermal insulation and anti-corrosion coating 3 is the following mass components: 72g of composite resin emulsion, 53.4g of curing aid, 40g of nano-alumina dispersion, 72.2g of active reinforcing powder, 0.5g of anti-settling agent, and 0.5g of cellulose ether; wherein the composite resin emulsion is the silicone acrylate hybrid epoxy resin and silicone emulsion prepared in Preparation Example 1 in a mass ratio of 1.5:1; the active reinforcing powder includes 20g of slag powder, 10g of steel slag powder, 2g of sodium silicate, 15.2g of basalt flakes and 25g of quartz powder; the mass ratio of the composite resin emulsion, the nano-alumina dispersion and the basalt flakes is 1.8:1:0.38; the curing aid is 10g of curing agent, 0.3g of wetting agent, 0.4g of dispersant, 0.3g of defoaming agent, 0.6g of film-forming aid and 41.8g of deionized water.

[0041] Example 10 The difference between this embodiment and embodiment 1 is that the thermal insulation and anti-corrosion coating 3 is the following mass components: 100g of composite resin emulsion, 53.4g of curing aid, 24g of nano-alumina dispersion, 72g of active reinforcing powder, 0.5g of anti-settling agent, and 0.5g of cellulose ether; wherein the composite resin emulsion is the silicone acrylate hybrid epoxy resin and silicone emulsion prepared in Preparation Example 1 in a mass ratio of 1.5:1; the active reinforcing powder includes 20g of slag powder, 10g of steel slag powder, 2g of sodium silicate, 15.2g of basalt flakes and 25g of quartz powder; the mass ratio of the composite resin emulsion, the nano-alumina dispersion and the basalt flakes is 2.5:0.6:0.38; the curing aid is 10g of curing agent, 0.3g of wetting agent, 0.4g of dispersant, 0.3g of defoaming agent, 0.6g of film-forming aid and 41.8g of deionized water.

[0042] Embodiment 11 The difference between this embodiment and embodiment 1 is that the finishing weather-resistant layer 5 includes 65g of water-based silicone acrylate hybrid epoxy resin, 37.8g of FEVE emulsion, 34g of curing aid, 0.2g of leveling agent, 4.2g of nano calcium carbonate and 4g of color paste; wherein the curing aid includes 9g of curing agent, 0.3g of wetting agent, 0.3g of dispersant, 0.2g of defoaming agent, 0.5g of film-forming aid and 23.7g of deionized water.

[0043] Comparative Example 1 The difference between the comparative example and Example 1 is that the composite resin emulsion is an organosilicon emulsion; Comparative Example 2 The difference between this comparative example and Example 1 is that the thermal insulation and anti-corrosion coating 3 is the following mass components: 100g of composite resin emulsion, 53.4g of curing aid, 72g of active reinforcing powder, 0.5g of anti-settling agent, and 0.5g of cellulose ether; wherein the composite resin emulsion is the silicone acrylate hybrid epoxy resin and silicone emulsion obtained in Preparation Example 1 in a mass ratio of 1.5:1; the active reinforcing powder includes 20g of slag powder, 10g of steel slag powder, 2g of sodium silicate, 15g of basalt flakes and 25g of quartz powder; the mass ratio of the composite resin emulsion and the basalt flakes is 2.5:0.38; the curing aid is 10g of curing agent, 0.3g of wetting agent, 0.4g of dispersant, 0.3g of defoaming agent, 0.6g of film-forming aid and 41.8g of deionized water.

[0044] Comparative Example 3 The difference between this comparative example and Example 1 is that the thermal insulation and anti-corrosion coating 3 is the following mass components: 100g of composite resin emulsion, 53.4g of curing aid, 40g of nano-alumina dispersion, 72g of active reinforcing powder, 0.5g of anti-settling agent, and 0.5g of cellulose ether; wherein the composite resin emulsion is the silicone acrylate hybrid epoxy resin and silicone emulsion obtained in Preparation Example 1 in a mass ratio of 1.5:1; the active reinforcing powder includes 35g of slag powder, 10g of steel slag powder, 2g of sodium silicate and 25g of quartz powder; the mass ratio of the composite resin emulsion and the nano-alumina dispersion is 2.5:1; the curing aid is 10g of curing agent, 0.3g of wetting agent, 0.4g of dispersant, 0.3g of defoaming agent, 0.6g of film-forming aid and 41.8g of deionized water.

[0045] Comparative Example 4 A thick coating with corrosion resistance and fire resistance for steel structure, comprising the following components: a heat-insulating and anti-corrosion coating 3, a light fire-proof coating 4 and a decorative weather-resistant layer 5 arranged in sequence on the surface of a steel substrate 1, wherein the heat-insulating and anti-corrosion coating 3 comprises the following mass components: 100 g of a composite resin emulsion, 53.4 g of a curing aid, 50 g of a nano-alumina dispersion, 72 g of an active enhancement powder, 0.5 g of an anti-settling agent, and 0.5 g of a cellulose ether; wherein the mass ratio of the composite resin emulsion is 1.5: The organic silicon acrylate hybrid epoxy resin and organic silicon emulsion prepared in Preparation Example 1 of 1; the active enhancement powder includes 20g slag powder, 10g steel slag powder, 2g sodium silicate, 15g basalt flakes and 25g quartz powder; the mass ratio of the composite resin emulsion, the nano-alumina dispersion and the basalt flakes is 2:1:0.3; the curing aid is 10g curing agent, 0.3g wetting agent, 0.4g dispersant, 0.3g defoaming agent, 0.6g film-forming aid and 41.8g deionized water; Lightweight fireproof coating 4: including 110g composite resin emulsion, 103g lightweight composite powder, 107g curing aid, and 35g nano-alumina dispersion; wherein, 80g of the organosilicon acrylate hybrid epoxy resin prepared in Preparation Example 1 and 30g of organosilicon emulsion; the lightweight composite powder is 25g of high-alumina cement, 7g of glass powder, 5g of hollow glass beads, 4g of barium sulfate, 10g of aluminum hydroxide, 1g of silica fume, 0.2g of cellulose ether, and 34.7g of light sand; the curing aid includes 9g of curing agent, 0.3g of wetting agent, 0.3g of dispersant, 0.2g of defoaming agent, 0.5g of film-forming aid, and 23.4g of deionized water; Finishing weather-resistant layer 5: including 65g of water-based silicone acrylate hybrid epoxy resin, 36g of FEVE emulsion, 34g of curing aid, 0.2g of leveling agent, 6g of nano calcium carbonate and 4g of color paste; wherein the curing aid includes 9g of curing agent, 0.3g of wetting agent, 0.3g of dispersant, 0.2g of defoaming agent, 0.5g of film-forming aid and 23.7g of deionized water; Mix the heat-insulating and anti-corrosion coating 3 paint evenly, spray it on the surface of the steel substrate 1, and ensure that the thickness is 18 mm; mix the lightweight fire-retardant coating 4 paint evenly, spray it on the surface of the heat-insulating and anti-corrosion coating 3 after drying and curing; ensure that the thickness is 10 mm, mix the finishing weather-resistant layer 5 paint evenly, spray it on the surface of the cured lightweight fire-retardant coating 4, and ensure that the thickness is 1 mm.

[0046] Comparative Example 5 A thick coating with corrosion resistance and fire resistance for steel structure, comprising the following components: a composite resin modified zinc-rich primer 2, a heat insulation and anti-corrosion coating 3, and a lightweight fire-proof coating 4 arranged in sequence on the surface of a steel substrate 1, wherein the composite resin modified zinc-rich primer 2 comprises the following mass components: 100g of composite resin emulsion, 108g of zinc-rich reinforcing powder, 40.9g of curing aid, and 5g of nano-alumina dispersion; wherein the composite resin emulsion comprises 70g of the organosilicon acrylate hybrid epoxy resin prepared in Preparation Example 1 and 30g of the organosilicon emulsion, and the zinc-rich reinforcing powder comprises slag powder, sodium silicate, and zinc powder in a mass ratio of 1.8:1:9; and the curing aid comprises 10g of curing agent, 0.1g of wetting agent, 0.3g of dispersant, 0.2g of defoaming agent, 0.6g of film-forming aid, and 29.7g of deionized water; The heat-insulating and anti-corrosion coating 3 is composed of the following mass components: 100 g of composite resin emulsion, 53.4 g of curing aid, 50 g of nano-alumina dispersion, 72 g of active reinforcing powder, 0.5 g of anti-settling agent, and 0.5 g of cellulose ether; wherein the composite resin emulsion is the silicone acrylate hybrid epoxy resin and silicone emulsion obtained in Preparation Example 1 in a mass ratio of 1.5:1; the active reinforcing powder includes 20 g of slag powder, 10 g of steel slag powder, 2 g of sodium silicate, 15 g of basalt flakes, and 25 g of quartz powder; the mass ratio of the composite resin emulsion, nano-alumina dispersion, and basalt flakes is 2:1:0.3; the curing aid is 10 g of curing agent, 0.3 g of wetting agent, 0.4 g of dispersant, 0.3 g of defoaming agent, 0.6 g of film-forming aid, and 41.8 g of deionized water; Lightweight fireproof coating 4: including 110g composite resin emulsion, 103g lightweight composite powder, 107g curing aid, and 35g nano-alumina dispersion; wherein, 80g of the organosilicon acrylate hybrid epoxy resin prepared in Preparation Example 1 and 30g of organosilicon emulsion; the lightweight composite powder is 25g of high-alumina cement, 7g of glass powder, 5g of hollow glass beads, 4g of barium sulfate, 10g of aluminum hydroxide, 1g of silica fume, 0.2g of cellulose ether, and 34.7g of light sand; the curing aid includes 9g of curing agent, 0.3g of wetting agent, 0.3g of dispersant, 0.2g of defoaming agent, 0.5g of film-forming aid, and 23.4g of deionized water; First, mix the composite resin modified zinc-rich primer 2 coating evenly in proportion, and evenly apply it on the surface of the steel substrate 1 by rolling, ensuring that the thickness is 2 mm; mix the heat-insulating anti-corrosion coating 3 coating evenly, and spray it on the surface of the composite resin modified zinc-rich primer 2 after drying and curing, ensuring that the thickness is 18 mm; mix the lightweight fire-retardant coating 4 coating evenly, and spray it on the surface of the heat-insulating anti-corrosion coating 3 after drying and curing; ensuring that the thickness is 10 mm.

[0047] Performance Testing The performance tests of the thick coatings with corrosion resistance and fire resistance for steel structures prepared in the embodiments and comparative examples were conducted by the following methods: physical and chemical properties, fire resistance and weather resistance were tested according to GB / T14907-2018, salt spray resistance was tested according to "Anti-corrosion Coatings for Steel Structures in Construction" JG / T224-2007, and the bonding strength was tested for the bonding strength between the composite resin modified zinc-rich primer and the steel substrate (1) and the bonding strength between the thermal insulation and anti-corrosion coating and the lightweight fire-retardant coating (2); thick The overall salt spray resistance (3) of the coating, as well as the salt spray resistance (4) of the heat-insulating and anti-corrosion coating and the lightweight fire-retardant coating, showed no peeling, bulging, peeling, cracking, red rust, etc. for a certain period of time; Weathering resistance test of the surface weather-resistant layer: artificial aging test with a xenon lamp for more than 1500 hours; The test results are as follows; The lightweight fire-retardant coating in Example 1 was burned under a flame of 1200 degrees for 3 hours, and the temperature on the back of the steel plate was 380 degrees; The lightweight fire-retardant coating in Example 2 was burned under a flame of 1200 degrees for 3 hours, and the temperature on the back of the steel plate was 260 degrees; Table 1 Performance test results As can be seen from Table 1, the thick coating with corrosion resistance and fire resistance for steel structure obtained in the above embodiment has excellent fire resistance and high salt spray resistance, good adhesion and density between coatings, and good long-term performance.

[0048] Compared with Examples 6-10 and Example 1 and Comparative Examples 1-3, it can be seen that silicone acrylate hybrid epoxy resin and silicone emulsion have excellent bonding properties with various materials and improve the density and impact resistance of resin materials, improve the salt spray resistance, acid and alkali resistance and temperature resistance of the coating, and thus improve the comprehensive properties of the coating such as strength and corrosion resistance; a certain proportion of composite resin emulsion, nano alumina dispersion, and basalt flakes enables the thermal insulation and anti-corrosion coating to maintain good interlayer adhesion and density, constitute a barrier layer that can efficiently isolate corrosive media, greatly increase the difficulty of corrosive media entering the coating film, and improve the heat resistance of the middle coating. Among them, the composite resin emulsion content is too low, the adhesion performance is insufficient, and the strength is poor. The nano alumina dispersion content is too low, resulting in insufficient heat resistance, and the dispersion of basalt flakes is weak, and the interface effect with the resin is relatively poor, resulting in the arrangement of basalt flakes difficult to control, affecting the corrosion resistance of the anti-corrosion coating.

[0049] By comparing Example 1 with Example 11 and Comparative Example 5, it can be seen that by adding silicone acrylate hybrid epoxy resin to FEVE resin, the chemical inertness of the coating surface is further improved, and a large number of FC bonds are introduced, which has stronger stability. The introduction of nano calcium carbonate significantly improves the compactness of the paint film after the resin is cured, prevents powdering and fading, and enhances the weather resistance and color retention of the protective surface layer, as well as the ability to resist various corrosive media, thereby ensuring that the entire fireproof system has excellent durability, can maintain the fireproof ability of the system for a long time, and extend the service life. Excessive FEVE emulsion content will cause the coating to be too rigid, not have good elasticity, unstable performance, insufficient weather resistance, and severe cracking, peeling, and powdering.

[0050] By comparing Example 1 with Examples 4-5 and Comparative Example 4, it can be seen that the interaction between the inorganic nano-material slag powder and sodium silicate in the range of the present application cuts off the channel formed by the volatilization of water after the resin film is formed, significantly improving the sealing effect of the water-based resin coating, and together with the zinc powder, it has a high anti-corrosion effect on the metal surface, and has the advantages of strong bonding with the metal substrate, good salt spray resistance, and good heat and humidity resistance. Among them, too little zinc powder content may affect the salt spray resistance of the primer and the salt spray resistance of the overall material.

[0051] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A thick coating with corrosion resistance and fire resistance for steel structures, characterized in that: The invention comprises a composite resin modified zinc-rich primer (2), a heat-insulating anti-corrosion coating (3), a lightweight fire-proof coating (4) and a finishing weather-resistant layer (5) which are sequentially arranged on the surface of a steel substrate (1); the heat-insulating anti-corrosion coating (3) comprises, by weight, 80-120 parts of a composite resin emulsion, 52.5-76.7 parts of a curing aid, 30-40 parts of a nano-alumina dispersion, 66.5-133.5 parts of an active reinforcing powder, 0.3-0.6 parts of an anti-settling agent and 0.3-0.6 parts of a cellulose ether, wherein the active reinforcing powder comprises slag powder, steel slag powder, sodium silicate, basalt flakes and quartz powder.

2. The thick coating with corrosion resistance and fire resistance for steel structure according to claim 1, characterized in that: The composite resin emulsion comprises silicone acrylate hybrid epoxy resin and silicone emulsion.

3. The thick coating with corrosion resistance and fire resistance for steel structure according to claim 2, characterized in that: The mass ratio of silicone acrylate hybrid epoxy resin and silicone emulsion is (1.5-4):

1.

4. The thick coating with corrosion resistance and fire resistance for steel structure according to claim 1, characterized in that: The mass ratio of the composite resin emulsion, the nano-alumina dispersion and the basalt flakes is (2-4):1:(0.2-0.45).

5. The thick coating with corrosion resistance and fire resistance for steel structure according to claim 1, characterized in that: The finishing weather-resistant layer (5) comprises 60-70 parts by weight of waterborne organosilicon acrylate hybrid epoxy resin, 30-40 parts by weight of FEVE emulsion, 33.7-44.7 parts by weight of curing aid, 0.2-0.4 parts by weight of leveling agent, 5-8 parts by weight of nano calcium carbonate and 3-6 parts by weight of color paste.

6. The thick coating with corrosion resistance and fire resistance for steel structure according to claim 5, characterized in that: The mass ratio of the FEVE emulsion and nano-calcium carbonate is (4-8):

1.

7. The thick coating with corrosion resistance and fire resistance for steel structure according to claim 1, characterized in that: The composite resin modified zinc-rich primer (2) comprises, by weight, 80-120 parts of composite resin emulsion, 92-108 parts of zinc-rich reinforcing powder, 39.3-47.7 parts of curing aid, and 5-8 parts of nano-alumina dispersion; the zinc-rich reinforcing powder comprises slag powder, sodium silicate and zinc powder.

8. The thick coating with corrosion resistance and fire resistance for steel structure according to claim 7, characterized in that: The mass ratio of the slag powder, sodium silicate and zinc powder is (1.8-4):1:(9-16).